2019
DOI: 10.1109/access.2019.2897327
|View full text |Cite
|
Sign up to set email alerts
|

Part of Speech Tagging in Urdu: Comparison of Machine and Deep Learning Approaches

Abstract: In Urdu, part of speech (POS) tagging is a challenging task as it is both inflectionally and derivationally rich morphological language. Verbs are generally conceived a highly inflected object in Urdu comparatively to nouns. POS tagging is used as a preliminary linguistic text analysis in diverse natural language processing domains such as speech processing, information extraction, machine translation, and others. It is a task that first identifies appropriate syntactic categories for each word in running text… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 50 publications
0
14
0
Order By: Relevance
“…Khan et al [21] dealt with a morphologically rich language, they examined and evaluated the effectiveness of machine learning and deep learning for morphologically rich language part-of-speech tagging.…”
Section: Related Workmentioning
confidence: 99%
“…Khan et al [21] dealt with a morphologically rich language, they examined and evaluated the effectiveness of machine learning and deep learning for morphologically rich language part-of-speech tagging.…”
Section: Related Workmentioning
confidence: 99%
“…The labeling of natural language text with POS tags can be a complicated task, requiring much effort, even for trained annotators (Rane et al, 2020). A large number of LRs are publicly available for high-resource languages such as English (Marcus and Marcinkiewicz), Chinese, Indian languages (Baskaran Sankaran and Subbarao, 2008;Khan et al, 2019) and others (Petrov et al, 2012). Unlike rich-resourced languages such as English and Chinese with abundant publicly accessible LRs, Sindhi is relatively low-resource , which lacks the POS tagged dataset that can be utilized to train a supervised or statistical algorithm.…”
Section: Related Workmentioning
confidence: 99%
“…We apply a deep learning approach to improve the performance of our biomedical NER system. Recent studies [39]- [42] using deep learning techniques have demonstrated the high performance for sequential labeling tasks contain the NER task. In particular, LSTM-CRF is known as a model with high performance in NER tasks [43], [44].…”
Section: ) Bidirectional Lstm-crf Network Based Biomedical Nermentioning
confidence: 99%